Microwave-hydrothermal synthesis of barium strontium titanate nanoparticles - Simões, Alexandre Zirpoli [UNESP]; Moura, F.; Onofre, T. B.; Ramirez, M. A. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2010)
Hydrothermal-microwave method (HTMW) was used to synthesize crystalline barium strontium titanate (Ba(0.8)Sr(0.2)TiO(3)) nanoparticles (BST) in the temperature range of 100-130 degrees C. The crystallization of BST with tetragonal structure was reached at all the synthesis temperatures along with the formation of BaCO(3) as a minor impurity at lower syntheses temperatures. Typical FT-IR spectra for tetragonal (BST) nanoparticles presented well defined bands, indicating a substantial short-range order in the system. TG-DTA analyses confirmed the presence of lattice OH- groups, commonly found in materials obtained by HTMW process. FE/SEM revealed that lower syntheses temperatures led to a morphology that consisted of uniform grains while higher syntheses temperature consisted of big grains isolated and embedded in a matrix of small grains. TEM has shown BST nanoparticles with diameters between 40 and 80 nm. These results show that the HTMW synthesis route is rapid, cost effective, and could serve as an alternative to obtain BST nanoparticles. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Nanoparticle; Chemical synthesis; Microwave; Electron microscopy; Crystal structure